A lithium ion electrically controlled adsorption separation membrane and its preparation method and application
By using an electronically controlled adsorption separation membrane with high-efficiency lithium ion transmission channels during the extraction and concentration of low-grade lithium resources, the problems of low-grade lithium transmission efficiency and great influence of concentration polarization are solved, and efficient enrichment of low-grade lithium is achieved , concentration and purification.
Patent Information
- Application Number
- CN202311195672.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-09-15
AI Technical Summary
The prior art faces problems such as low lithium ion transmission efficiency and great impact on concentration and polarization in the process of high-efficiency and low-consumption extraction, concentration and purification of low-grade lithium resources.
Using an electronically controlled adsorption separation membrane with stable structure and high-efficiency lithium ion transmission channel, the membrane integrates electric-control adsorption enrichment of Li+ and selective electrodialysis (SED) concentrated Li+, which enhances the continuous and rapid selectivity of lithium ions through electric field coupling. The electronically controlled adsorption-desorption process is used to increase the Li+ concentration of the ion exchange membrane interface through the Li+ enrichment area of the electrode interface during electronically controlled desorption, and slow down/eliminate the influence of SED concentration polarization.
It achieves efficient enrichment, concentration and purification of low-grade lithium, improves lithium concentration and purification efficiency, reduces energy consumption, and slows down the impact of concentration polarization during SED operation.
Smart Images

Figure CN117205762B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion exchange membranes, and in particular relates to a lithium ion electrically controlled adsorption separation membrane and a preparation method and application thereof. Background Art
[0002] In recent years, global lithium consumption has grown rapidly, and my country's consumption has increased by more than 20% annually. At present, China's lithium resource development mostly uses salt lake brine as raw material, which has a long extraction cycle and a large amount of lithium loss. With the continuous development of salt lake resources, direct extraction of lithium resources using raw brine as raw material has become a research hotspot, but low-grade raw brine Li + The low content and high content of co-existing impurity ions make the development of efficient and low-consumption extraction technology for low-grade lithium resources face huge challenges.
[0003] For the development of low-grade lithium resources, technologies such as adsorption and electrochemical adsorption have great development prospects. The adsorption method has developed rapidly in the field of lithium extraction from salt lakes. For example, aluminum-based adsorbents have been applied on a large scale in industrial applications, but they have problems such as low adsorption capacity, large fresh water consumption, and high overall investment. Manganese-based and titanium-based adsorbents also face problems such as decreased adsorption capacity after granulation, the need for acid washing and regeneration, and poor cycle stability. The electrochemical adsorption method uses potential difference as the driving force, breaking the concentration equilibrium limit of the traditional adsorption method. It has the advantages of fast insertion-extraction rate, no need for chemical regeneration, and low energy consumption; but its operation process is intermittent operation, and there is also a small amount of raw liquid entrainment, which affects the overall efficiency and lithium purity of the recovered liquid. In addition, the lithium-rich solution obtained by the adsorption method and electrochemical adsorption method generally needs to be further concentrated and purified by other technologies (such as reverse osmosis, electrodialysis, selective electrodialysis (Selectiveelectrodialysis, SED), etc.) to obtain lithium concentrate that can be used for lithium precipitation. Among them, the use of adsorption-selective electrodialysis step-by-step coupling process to achieve separation and enrichment of low-grade lithium resources has attracted attention. Li in raw material solution + The concentration and purity are the key conditions affecting the SED concentration efficiency and energy consumption. Affected by the high ion transfer coefficient of the ion exchange membrane, an "ion depletion zone" is easily formed on the surface of the ion exchange membrane on the raw liquid side during the SED operation, causing a "concentration polarization" phenomenon, thus affecting the lithium extraction process.
[0004] Therefore, how to improve the Li content of SED feed solution + Concentration and purity, and reducing / suppressing the impact of "concentration polarization" are key issues in achieving lithium concentration and purification. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lithium ion electrically controlled adsorption separation membrane and its preparation method and application. The present invention constructs an electrically controlled adsorption separation membrane with a stable structure and an efficient lithium ion transmission channel. The electrically controlled adsorption separation membrane collects lithium ions by electrically controlled adsorption.+ Concentrated Li with SED + Integrates the Li + The continuous and rapid selective electro-controlled adsorption-desorption process achieves efficient enrichment, and the Li + The enriched area increases the Li + concentration to slow down / eliminate the influence of SED concentration polarization, improve the efficiency of lithium concentration and purification, and achieve efficient enrichment, concentration and purification of low-grade lithium.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a lithium ion electrically controlled adsorption separation membrane, wherein the lithium ion electrically controlled adsorption separation membrane comprises an electrochemical adsorption layer and an ion exchange membrane layer;
[0008] The electrochemical adsorption layer comprises a composite membrane electrode layer and a two-dimensional material support layer stacked in sequence, and the two-dimensional material support layer is connected to the ion exchange membrane layer;
[0009] The composite membrane electrode layer is obtained by compounding an electrode active material and a two-dimensional material.
[0010] The present invention constructs an electrically controlled adsorption separation membrane with a stable structure and an efficient lithium ion transmission channel. The electrically controlled adsorption separation membrane collects lithium ions through electrically controlled adsorption. + Concentrated Li with SED + Integrates the Li + The continuous and rapid selective electro-controlled adsorption-desorption process achieves efficient enrichment, and the Li + The enriched area increases the Li + concentration to slow down / eliminate the influence of SED concentration polarization, improve the efficiency of lithium concentration and purification, and achieve efficient enrichment, concentration and purification of low-grade lithium.
[0011] In the present invention, the electrode active material and the two-dimensional material are combined to effectively enhance the conductivity of the composite membrane electrode layer, improve its lithium extraction rate and cycle stability. By regulating the interlayer spacing and surface characteristics of the two-dimensional material, a nano-confined water transmission channel can be constructed to inhibit the free permeation of the raw material liquid or water.
[0012] In the present invention, a stable and precisely separated ion exchange membrane layer can be constructed on the two-dimensional material support layer. The ion exchange membrane layer has the characteristics of high density of charged groups, controllable pore size, low resistance, etc. It is a "charge channel" for rapid transfer of lithium ions, which can improve the lithium ion transmission efficiency and achieve high selectivity, low energy consumption and continuous extraction of lithium.
[0013] As a preferred technical solution of the present invention, the thickness ratio of the electrochemical adsorption layer and the ion exchange membrane layer is (1-10):1, for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, etc.
[0014] In the present invention, if the thickness ratio of the electrochemical adsorption layer to the ion exchange membrane layer is too small, that is, the thickness of the ion exchange membrane layer is too large, the ion flux becomes small; if the thickness ratio of the electrochemical adsorption layer to the ion exchange membrane layer is too large, that is, the thickness of the ion exchange membrane layer is too small, the long-term operation stability cannot be guaranteed.
[0015] As a preferred technical solution of the present invention, the electrode active material includes LiMn2O4, LiNixCo y Mn z Any one of O2, Li2MnO3, MnO2 or LiFePO4, or a combination of at least two thereof.
[0016] It should be noted that for LiNixCo y Mn z As for O2, the values of x, y and z are not limited, and only x+y+z=1 is required.
[0017] Preferably, the electrode active material has a multi-level pore structure.
[0018] In the present invention, the electrode active material with a multi-level pore structure can increase the contact area between the material and the solution, accelerate the lithium ion transfer rate, increase the adsorption capacity and thus enhance the concentration effect of the electrically controlled adsorption separation membrane.
[0019] Preferably, the particle size D50 of the electrode active material is 50-400 nm, for example, 50 nm, 100 nm, 200 nm, 300 nm or 400 nm.
[0020] In the present invention, the electrode active material of suitable size can match the size of the two-dimensional material during the self-assembly process, thereby enhancing the dispersibility and stability of the electrode active material.
[0021] Preferably, the mass ratio of the electrode active material to the two-dimensional material support layer is (1-10):1, for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, etc.
[0022] In the present invention, if the mass ratio of the electrode active material to the two-dimensional material support layer is too small, that is, the amount of the electrode active material added is too small, the interface Li +If the mass ratio of the electrode active material and the two-dimensional material support layer is too large, that is, too much electrode active material is added, the flexibility of the membrane electrode layer will be reduced and the mechanical properties will be reduced.
[0023] Preferably, the material of the two-dimensional material and the material of the two-dimensional material support layer are independently reduced graphene oxide or Mxene.
[0024] As a preferred technical solution of the present invention, the thickness ratio of the composite membrane electrode layer and the two-dimensional material support layer is (1-5):1, for example, it can be 1:1, 2:1, 3:1, 4:1 or 5:1.
[0025] In the present invention, if the thickness ratio of the composite membrane electrode layer and the two-dimensional material support layer is too small, that is, the thickness of the two-dimensional material support layer is too large, the transmembrane transmission resistance increases and the ion flux decreases; if the thickness ratio of the composite membrane electrode layer and the two-dimensional material support layer is too large, that is, the thickness of the two-dimensional material support layer is too small, the uniform distribution of the polyamide layer cannot be guaranteed, affecting the experimental reproducibility.
[0026] As a preferred technical solution of the present invention, the ion exchange membrane layer is a polyamide separation layer.
[0027] In the present invention, the polyamide separation layer has a stable structure, uniform pores and an efficient lithium ion transmission channel.
[0028] Preferably, the average pore size of the ion exchange membrane layer is 0.2-1.5 nm, for example, 0.2 nm, 0.5 nm, 1 nm or 1.5 nm.
[0029] In a second aspect, the present invention provides a method for preparing the lithium ion electrically controlled adsorption separation membrane as described in the first aspect, the preparation method comprising the following steps:
[0030] (1) coating a two-dimensional material solution on a base film so as to form a two-dimensional material support layer on the base film;
[0031] (2) coating a two-dimensional material solution containing an electrode active material on the two-dimensional material support layer to obtain an electrochemical adsorption layer having a composite membrane electrode layer;
[0032] (3) Mixing the aqueous phase monomer material, the oil phase monomer material and the electrochemical adsorption layer to carry out an interfacial polymerization reaction to obtain a lithium ion electrically controlled adsorption separation membrane having an ion exchange membrane layer.
[0033] In the present invention, by means of aqueous phase monomers with higher charge density, the charge of the separation layer and its electrostatic repulsion to multivalent hetero ions can be enhanced, thereby breaking the "trade-off" effect and reducing the overall membrane resistance.
[0034] As a preferred technical solution of the present invention, the material of the base film in step (1) is selected from any one of cellulose acetate, polyethersulfone or polyacrylonitrile, or a combination of at least two of them.
[0035] Preferably, the coating method in step (2) includes vacuum filtration.
[0036] Preferably, after the coating in step (2) is completed, the composite membrane electrode layer is irradiated by ultraviolet light source.
[0037] In the present invention, the purpose of irradiating the composite membrane electrode layer with an ultraviolet light source is to transform the two-dimensional material made of graphene oxide into a two-dimensional material made of reduced graphene oxide, so as to improve the conductivity of the two-dimensional material.
[0038] As a preferred technical solution of the present invention, the aqueous phase monomer material in step (3) is an amine polymer, preferably an amine polymer containing a quaternary amine group.
[0039] Preferably, the method for preparing the amine polymer containing quaternary amine groups comprises:
[0040] The amine raw material and the halogenating agent are mixed in an aqueous solution and subjected to a quaternary amination reaction to obtain the amine polymer containing a quaternary amine group.
[0041] Preferably, the amine polymer includes any one of polyethyleneimine, piperazine, m-phenylenediamine, polyallylamine, p-phenylenediamine or hexamethylenediamine, or a combination of at least two thereof.
[0042] Preferably, the amine polymer containing quaternary amine groups comprises quaternized polyethyleneimine and / or quaternized polyallylamine.
[0043] Preferably, the halogenating agent comprises ethylamine bromide and / or propylamine bromide.
[0044] Preferably, the mass ratio of the halogenating agent to the amine raw material is 1:(8-12), for example, it can be 1:8, 1:9, 1:10, 1:11 or 1:12.
[0045] Preferably, the temperature of the quaternization reaction is 60-100°C, for example, 60°C, 70°C, 80°C, 90°C or 100°C.
[0046] Preferably, the quaternization reaction time is 4-24 h, for example, 4 h, 8 h, 12 h, 16 h, 50 h or 24 h.
[0047] In the present invention, by regulating the time of the quaternization reaction or the concentration of the halogenation agent, the density of the charged groups of the amine polymer containing the quaternary amine group can be regulated, thereby increasing the positive charge density of the polyamide separation layer and achieving efficient transmission of lithium ions.
[0048] Preferably, the oil phase monomer material in step (3) is an acyl chloride compound.
[0049] Preferably, the acyl chloride compound includes any one of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride or tetraphthaloyl chloride, or a combination of at least two thereof.
[0050] Preferably, the mass ratio of the aqueous phase monomer material to the oil phase monomer material in step (3) is (8-12):1, for example, it can be 8:1, 9:1, 10:1, 11:1 or 12:1.
[0051] As a preferred technical solution of the present invention, the mixing method in step (3) includes:
[0052] The electrochemical adsorption layer with the composite membrane electrode layer is immersed in the aqueous phase solution containing the aqueous phase monomer material. After the immersion is completed, the oil phase solution containing the oil phase monomer material is placed on the surface of the immersed electrochemical adsorption layer to perform an interfacial polymerization reaction.
[0053] Preferably, the temperature of the interfacial polymerization reaction in step (3) is 20-25°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C or 25°C.
[0054] Preferably, the interfacial polymerization reaction time in step (3) is 1-3 min, for example, 1 min, 2 min or 3 min.
[0055] Preferably, the aqueous phase solution further contains an aqueous phase solution additive.
[0056] In the present invention, the purpose of adding the aqueous solution additive to the aqueous solution is to regulate the diffusion process of the interfacial polymerization reaction.
[0057] Preferably, the aqueous solution additive includes organic additives and / or inorganic additives.
[0058] Preferably, the inorganic additive includes LiCl and / or MgCl2.
[0059] Preferably, the organic additive is an amphoteric organic additive, and the amphoteric organic additive includes any one of nonylphenol polyoxyethylene ether, dodecanediodium phytic acid, sodium dodecyl sulfonate or hexadecyltrimethylammonium bromide.
[0060] Preferably, in the aqueous phase solution, the mass concentration of the aqueous phase solution additive is 0.1-1%, for example, it can be 0.1%, 0.5%, 0.7%, 0.8%, 0.9% or 1%, etc.
[0061] In the present invention, by regulating the amount of additives added to the aqueous solution, the diffusion behavior of the amine polymer can be inhibited by the hydrogen bonding between the inorganic additives and the amine polymer, or the amphiphilic molecular layer formed at the water-oil interface by the amphiphilic organic additives can be used to uniformly regulate the diffusion behavior of the aqueous monomer material into the oil phase solution, and combined with molecular dynamics simulation of the interaction between the additives and the aqueous monomer and the diffusion path, a stable and precisely separated ion exchange membrane layer can be constructed.
[0062] In a third aspect, the present invention provides an application of the lithium ion electrically controlled adsorption separation membrane as described in the first aspect in the development of low-grade lithium resources.
[0063] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] (1) The present invention constructs an electrically controlled adsorption separation membrane with a stable structure and an efficient lithium ion transmission channel. The electrically controlled adsorption separation membrane collects Li + Concentrated Li with SED + Integrates the Li + The continuous and rapid selective electro-controlled adsorption-desorption process achieves efficient enrichment, and the Li + The enriched area increases the Li + concentration to slow down / eliminate the influence of SED concentration polarization, improve the efficiency of lithium concentration and purification, and achieve efficient enrichment, concentration and purification of low-grade lithium.
[0066] (2) In the present invention, the electrode active material and the two-dimensional material are combined to effectively enhance the conductivity of the composite membrane electrode layer, improve its lithium extraction rate and cycle stability. By regulating the interlayer spacing and surface properties of the two-dimensional material, a nano-confined water transmission channel can be constructed to inhibit the free permeation of the raw material liquid or water.
[0067] (3) In the present invention, a stable and precisely separated ion exchange membrane layer can be synthesized on a two-dimensional material support layer. The ion exchange membrane layer has the characteristics of high density of charged groups, controllable pore size, and low resistance. It is a "charge channel" for rapid transfer of lithium ions, which can improve the lithium ion transmission efficiency and achieve high selectivity, low energy consumption, and continuous extraction of lithium. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is a physical picture of the electrically controlled adsorption separation membrane prepared in Example 1 of the present invention.
[0069] Figure 2 This is a scanning electron microscope image of the electrically controlled adsorption separation membrane prepared in Example 1 of the present invention.
[0070] Figure 3 The Li of the electrically controlled adsorption separation membrane provided in Example 1 of the present invention + Flux and Mg 2+ Histogram of flux.
[0071] Figure 4 This is a bar chart of the lithium-magnesium separation coefficient of the electrically controlled adsorption separation membrane provided in Example 1 of the present invention under constant current conditions.
[0072] Figure 5 The Li of the reduced graphene oxide support layer membrane provided in Comparative Example 1 of the present invention + Flux and Mg 2+ Histogram of flux.
[0073] Figure 6 The reduced graphene oxide support layer / ion exchange membrane layer provided in Comparative Example 1 of the present invention is Li + Flux and Mg 2+ Histogram of flux.
[0074] Figure 7 This is a bar chart of the lithium-magnesium separation coefficient of the reduced graphene oxide support layer / ion exchange membrane layer provided in Comparative Example 1 of the present invention under constant current conditions. DETAILED DESCRIPTION
[0075] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0076] Example 1
[0077] This embodiment provides a lithium ion electrically controlled adsorption separation membrane, such as Figure 1 As shown, the lithium ion electrically controlled adsorption separation membrane comprises an electrochemical adsorption layer and an ion exchange membrane layer with a thickness ratio of 5:1;
[0078] The electrochemical adsorption layer comprises a composite membrane electrode layer and a two-dimensional material support layer which are stacked in sequence with a thickness ratio of 2:1, and the two-dimensional material support layer is connected to the ion exchange membrane layer;
[0079] The composite membrane electrode layer is obtained by compounding the electrode active material and the two-dimensional material;
[0080] The electrode active material is lithium manganese oxide (LiMn2O4) with a multi-level pore structure, and its particle size D50 is 200nm. Based on the mass of the composite membrane electrode layer, the mass ratio of the electrode active material to the two-dimensional material support layer is 1:1;
[0081] The material of the two-dimensional material and the material of the two-dimensional material support layer are both reduced graphene oxide;
[0082] The ion exchange membrane is a polyamide separation layer with an average pore size of 1 nm.
[0083] Figure 2 The scanning electron microscope image of the lithium ion electrically controlled adsorption separation membrane prepared in this embodiment is shown. As can be seen from the figure, the electrically controlled adsorption separation membrane is composed of an ion exchange membrane layer and an electrochemical adsorption layer ( Figure 2 a), the support layer in the electrochemical adsorption layer is relatively regular as a whole, with two-dimensional reduced graphene oxide sheets stacked layer by layer, which not only serves as a flexible substrate for the polyamide separation layer, but also provides orderly nanochannels for lithium ion transmission ( Figure 2 b, 2c); The polyamide separation layer has a typical nodular structure, and the nodular structure is uniform in size and evenly distributed, indicating that a relatively complete polyamide structure is formed on the membrane surface ( Figure 2 d); The electrochemical adsorption layer presents a sandwich structure, and lithium manganese oxide is evenly distributed between the reduced graphene oxide sheets. Reduced graphene oxide provides a continuous conductive network for lithium manganese oxide, accelerating charge transfer and ion transport ( Figure 2 e, 2f).
[0084] This embodiment also provides a method for preparing the above-mentioned lithium ion electrically controlled adsorption separation membrane, the preparation method comprising the following steps:
[0085] (1) filtering an aqueous solution containing graphene oxide onto a cellulose acetate base film, so that a graphene oxide support layer is formed on the base film;
[0086] (2) dispersing lithium manganese oxide uniformly in an aqueous solution containing graphene oxide under mechanical stirring to obtain a mixed solution, filtering the mixed solution onto the graphene oxide support layer using a vacuum filtration technique to obtain a composite membrane electrode layer, and then irradiating the composite membrane electrode layer with an ultraviolet light source for 4 hours to directionally reduce the graphene oxide layer in the composite membrane electrode layer to form reduced graphene oxide, thereby obtaining an electrochemical adsorption layer having a structure of LiMn2O4@rGO / rGO;
[0087] (3) mixing polyethyleneimine and a halogenating agent in an aqueous solution (the mass ratio of the halogenating agent to polyethyleneimine is 1:10), and performing a quaternization reaction at 80° C. for 4 hours to obtain quaternized polyethyleneimine as an aqueous phase monomer material;
[0088] Wherein, the halogenating agent is ethylammonium bromide;
[0089] (4) soaking the electrochemical adsorption layer having the structure of LiMn2O4@rGO / rGO in an aqueous solution containing an aqueous monomer material and an aqueous solution additive, taking out the electrochemical adsorption layer after soaking, fixing it on a polytetrafluoroethylene plate with an adhesive tape, pouring an oil phase solution containing an oil phase monomer material, and then performing an interfacial polymerization reaction at 25°C for 1 min to obtain a lithium ion electrically controlled adsorption separation membrane having an ion exchange membrane layer;
[0090] The oil phase monomer material is trimesoyl chloride, the mass ratio of the water phase monomer material to the oil phase monomer material is 10:1, and the water phase solution additive is sodium dodecyl sulfate, and the mass concentration thereof is 0.5%.
[0091] Example 2
[0092] This embodiment provides a lithium ion electrically controlled adsorption separation membrane, wherein the lithium ion electrically controlled adsorption separation membrane comprises an electrochemical adsorption layer and an ion exchange membrane layer with a thickness ratio of 5:1;
[0093] The electrochemical adsorption layer comprises a composite membrane electrode layer and a two-dimensional material support layer which are stacked in sequence with a thickness ratio of 2:1, and the two-dimensional material support layer is connected to the ion exchange membrane layer;
[0094] The composite membrane electrode layer is obtained by compounding the electrode active material and the two-dimensional material;
[0095] The electrode active material is lithium manganate (LiMn2O4) with a multi-level pore structure, and its particle size D50 is 400nm. Based on the mass of the composite membrane electrode layer, the mass ratio of the electrode active material to the two-dimensional material support layer is 2:1;
[0096] The materials of the two-dimensional material and the two-dimensional material support layer are both reduced graphene oxide;
[0097] The ion exchange membrane is a polyamide separation layer with an average pore size of 1 nm.
[0098] This embodiment also provides a method for preparing the above-mentioned lithium ion electrically controlled adsorption separation membrane, the preparation method comprising the following steps:
[0099] (1) filtering an aqueous solution containing graphene oxide onto a cellulose acetate base film, so that a graphene oxide support layer is formed on the base film;
[0100] (2) dispersing lithium manganese oxide uniformly in an aqueous solution containing graphene oxide under mechanical stirring to obtain a mixed solution, filtering the mixed solution onto the graphene oxide support layer using a vacuum filtration technique to obtain a composite membrane electrode layer, and then irradiating the composite membrane electrode layer with an ultraviolet light source for 4 hours to directionally reduce the graphene oxide layer in the composite membrane electrode layer to form reduced graphene oxide, thereby obtaining an electrochemical adsorption layer having a structure of LiMn2O4@rGO / rGO;
[0101] (3) mixing polyethyleneimine and a halogenating agent (the mass ratio of the halogenating agent to polyethyleneimine is 1:8) in an aqueous solution, and performing a quaternization reaction at 80° C. for 8 hours to obtain quaternized polyethyleneimine as an aqueous phase monomer material;
[0102] Wherein, the halogenating agent is ethylammonium bromide;
[0103] (4) immersing the electrochemical adsorption layer having the structure of LiMn2O4@rGO / rGO in an aqueous solution containing an aqueous monomer material and an aqueous solution additive, placing an oily solution containing an oily monomer material on the surface of the electrochemical adsorption layer after immersion, and performing an interfacial polymerization reaction at 25° C. for 1 min to obtain a lithium ion electrically controlled adsorption separation membrane having an ion exchange membrane layer;
[0104] The oil phase monomer material is trimesoyl chloride, the mass ratio of the water phase monomer material to the oil phase monomer material is 10:1, and the water phase solution additive is sodium dodecyl sulfate, and its mass concentration is 0.1%.
[0105] Example 3
[0106] This embodiment provides a lithium ion electrically controlled adsorption separation membrane, wherein the lithium ion electrically controlled adsorption separation membrane comprises an electrochemical adsorption layer and an ion exchange membrane layer with a thickness ratio of 5:1;
[0107] The electrochemical adsorption layer comprises a composite membrane electrode layer and a two-dimensional material support layer which are stacked in sequence with a thickness ratio of 2:1, and the two-dimensional material support layer is connected to the ion exchange membrane layer;
[0108] The composite membrane electrode layer is obtained by compounding the electrode active material and the two-dimensional material;
[0109] The electrode active material is lithium manganate (LiMn2O4) with a multi-level pore structure, and its particle size D50 is 200nm. Based on the mass of the composite membrane electrode layer, the mass ratio of the electrode active material to the two-dimensional material support layer is 1:1;
[0110] The materials of the two-dimensional material and the two-dimensional material support layer are both reduced graphene oxide;
[0111] The ion exchange membrane is a polyamide separation layer with an average pore size of 1 nm.
[0112] This embodiment also provides a method for preparing the above-mentioned lithium ion electrically controlled adsorption separation membrane, the preparation method comprising the following steps:
[0113] (1) filtering an aqueous solution containing graphene oxide onto a cellulose acetate base film, so that a graphene oxide support layer is formed on the base film;
[0114] (2) dispersing lithium manganese oxide uniformly in an aqueous solution containing graphene oxide under mechanical stirring to obtain a mixed solution, filtering the mixed solution onto the graphene oxide support layer using a vacuum filtration technique to obtain a composite membrane electrode layer, and then irradiating the composite membrane electrode layer with an ultraviolet light source for 4 hours to directionally reduce the graphene oxide layer in the composite membrane electrode layer to form reduced graphene oxide, thereby obtaining an electrochemical adsorption layer having a structure of LiMn2O4@rGO / rGO;
[0115] (3) mixing polyethyleneimine and a halogenating agent having a mass fraction of 1% (the mass ratio of the halogenating agent to polyethyleneimine is 1:12) in an aqueous solution, and performing a quaternization reaction at 80° C. for 10 hours to obtain the quaternized polyethyleneimine as an aqueous phase monomer material;
[0116] Wherein, the halogenating agent is ethylammonium bromide;
[0117] (4) immersing the electrochemical adsorption layer having the structure of LiMn2O4@rGO / rGO in an aqueous solution containing an aqueous monomer material and an aqueous solution additive, placing an oily solution containing an oily monomer material on the surface of the electrochemical adsorption layer after immersion, and performing an interfacial polymerization reaction at 25° C. for 1 min to obtain a lithium ion electrically controlled adsorption separation membrane having an ion exchange membrane layer;
[0118] The oil phase monomer material is terephthaloyl chloride, the mass ratio of the water phase monomer material to the oil phase monomer material is 10:1, and the water phase solution additive is phytic acid dodecasodium salt, and its mass concentration is 0.5%.
[0119] Example 4
[0120] The difference between this embodiment and embodiment 1 is that the thickness of the ion exchange membrane is adjusted so that the thickness ratio of the electrochemical adsorption layer and the ion exchange membrane layer is 20:1.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Example 5
[0123] The difference between this embodiment and embodiment 1 is that the thickness of the ion exchange membrane is adjusted so that the thickness ratio of the electrochemical adsorption layer and the ion exchange membrane layer is 1:3.
[0124] The rest of the preparation methods and parameters were the same as those in Example 1.
[0125] Example 6
[0126] The difference between this embodiment and embodiment 1 is that the mass ratio of the electrode active material to the two-dimensional material support layer is 0.5:1.
[0127] The rest of the preparation methods and parameters were the same as those in Example 1.
[0128] Example 7
[0129] The difference between this embodiment and embodiment 1 is that the mass ratio of the electrode active material to the two-dimensional material support layer is 15:1.
[0130] The rest of the preparation methods and parameters were the same as those in Example 1.
[0131] Example 8
[0132] The difference between this embodiment and embodiment 1 is that the thickness of the two-dimensional material support layer is adjusted so that the thickness ratio of the composite membrane electrode layer and the two-dimensional material support layer is 0.5:1.
[0133] The rest of the preparation methods and parameters were the same as those in Example 1.
[0134] Example 9
[0135] The difference between this embodiment and Embodiment 1 is that the thickness of the two-dimensional material support layer is adjusted so that the thickness ratio of the composite membrane electrode layer and the two-dimensional material support layer is 6:1.
[0136] The rest of the preparation methods and parameters were the same as those in Example 1.
[0137] Example 10
[0138] The difference between this embodiment and embodiment 1 is that step (3) is not performed, that is, the polyethyleneimine is not subjected to quaternization treatment.
[0139] The rest of the preparation methods and parameters were the same as those in Example 1.
[0140] Embodiment 11
[0141] The difference between this embodiment and embodiment 1 is that no aqueous solution additive is added to the aqueous solution in step (4).
[0142] The rest of the preparation methods and parameters were the same as those in Example 1.
[0143] Example 12
[0144] The difference between this embodiment and embodiment 1 is that the mass concentration of the aqueous solution additive in step (4) is 0.05%.
[0145] The rest of the preparation methods and parameters were the same as those in Example 1.
[0146] Embodiment 13
[0147] The difference between this embodiment and embodiment 1 is that the mass concentration of the aqueous solution additive in step (4) is 2%.
[0148] The rest of the preparation methods and parameters were the same as those in Example 1.
[0149] Comparative Example 1
[0150] The difference between this comparative example and Example 1 is that steps (2) to (4) are replaced by the following steps:
[0151] a. irradiating the graphene oxide support layer with an ultraviolet light source for 4 hours to reduce the graphene oxide support layer to a reduced graphene oxide support layer film;
[0152] b. Immerse the reduced graphene oxide support layer membrane in an aqueous solution containing polyethyleneimine, take it out after 5 minutes, scrape it dry with a rubber roller and let it stand for 3 minutes; then use tape to fix the membrane on a polytetrafluoroethylene plate after standing, pour it into an oil phase solution containing trimesoyl chloride to react for 1 minute, remove the oil phase solution, and heat treat it at 80°C for 5 minutes to obtain a reduced graphene oxide support layer / ion exchange membrane layer.
[0153] The rest of the preparation methods and parameters were the same as those in Example 1.
[0154] Comparative Example 2
[0155] The difference between this comparative example and Example 1 is that lithium manganate is not added in step (2), that is, the composite membrane electrode layer only contains a membrane made of reduced graphene oxide.
[0156] The rest of the preparation methods and parameters were the same as those in Example 1.
[0157] Comparative Example 3
[0158] The difference between this comparative example and Example 1 is that step (1) is not performed, that is, the electrochemical adsorption layer does not contain a two-dimensional material support layer.
[0159] The rest of the preparation methods and parameters were the same as those in Example 1.
[0160] Performance Testing
[0161] The membranes prepared in the above embodiments and comparative examples were tested. The equipment of the experiment included a peristaltic pump, a DC power supply and an electrically controlled adsorption separation membrane device. The polar liquid was a 0.15 mol / L Na2SO4 solution, the initial raw material liquid was a mixed solution of 0.05 mol / L LiCl and 0.05 mol / L MgCl2, and the recovery liquid was a 0.1 mol / L KCl solution. The membranes provided in the above embodiments and comparative examples were installed in the electrically controlled adsorption separation membrane device for testing. After ensuring the airtightness of the device, the experiment was carried out. After a period of time, samples were taken for analysis to obtain Li + The present invention is to test the lithium ion electrically controlled adsorption separation membrane prepared in Example 1 according to the above experimental steps at 2 mA·cm -2 The experiment was carried out under constant current conditions, and samples were taken every 20 minutes for analysis. The analysis results are as follows Figure 3 and Figure 4 As shown in the figure, it can be seen that after 1h, Li + The flux is 1.40×10 -8 mol cm -2 ·s -1 , the lithium-magnesium separation factor is 16.62, and Li + The flux is 1.41×10 -8 mol cm -2 ·s -1 , the lithium-magnesium separation coefficient is 13.32.
[0162] The reduced graphene oxide support layer membrane prepared in Comparative Example 1 of the present invention is also subjected to the above-mentioned experimental steps at 2 mA·cm -2 The experiment was carried out under constant current conditions, and samples were taken and analyzed after 0.5h and 1h. The analysis results are as follows Figure 5 As shown in the figure, we can see that the obtained Li + The flux is 1.75×10 -8 mol cm -2 ·S -2 , 1.72×10 -8 mol cm -2 ·S -2 , the lithium-magnesium separation coefficient is 1.02.
[0163] The reduced graphene oxide support layer / ion exchange membrane layer prepared in Comparative Example 1 of the present invention was subjected to the above-mentioned experimental steps at 2 mA·cm -2 The experiment was carried out under constant current conditions. Samples were taken and analyzed after 1h and 2h. The analysis results are as follows Figure 6 and Figure 7 As shown in the figure, it can be seen that after 1h, Li + The flux is 1.24×10 -8 mol cm -2 ·s-1 , the lithium-magnesium separation factor is 7.29, and Li + The flux is 1.23×10 -8 mol cm -2 ·s -1 , the lithium-magnesium separation coefficient is 9.46.
[0164] Using the above experimental steps, the membranes provided in the examples and comparative examples were tested at 2 mA·cm -2 The experiment was carried out under constant current conditions. Samples were taken for analysis after 1 hour. The analysis results are shown in Table 1.
[0165] Table 1
[0166]
[0167] analyze:
[0168] As can be seen from the above table, the present invention constructs an electrically controlled adsorption separation membrane with a stable structure and an efficient lithium ion transmission channel. The electrically controlled adsorption separation membrane collects Li + Concentrated Li with SED + Integrates the Li + The continuous and rapid selective electro-controlled adsorption-desorption process achieves efficient enrichment, and the Li + The enriched area increases the Li + concentration to slow down / eliminate the influence of SED concentration polarization, improve the efficiency of lithium concentration and purification, and achieve efficient enrichment, concentration and purification of low-grade lithium.
[0169] It can be seen from the data results of Example 1 and Examples 4-5 that if the thickness ratio of the electrochemical adsorption layer and the ion exchange membrane layer is too small, that is, the thickness of the ion exchange membrane layer is too large, the ion flux decreases; if the thickness ratio of the electrochemical adsorption layer and the ion exchange membrane layer is too large, that is, the thickness of the ion exchange membrane layer is too small, the lithium ion flux increases and the selectivity decreases.
[0170] From the data results of Examples 1 and 6-7, it can be seen that if the mass content of the electrode active material is too low, Li + The concentration effect is limited and the selectivity decreases; if the mass content of the electrode active material is too high, the water barrier performance of the material is limited, the ion flux increases, and the selectivity decreases.
[0171] It can be seen from the data results of Example 1 and Examples 8-9 that if the thickness ratio of the composite membrane electrode layer and the two-dimensional material support layer is too small, that is, the thickness of the two-dimensional material support layer is too large, the mass transfer resistance increases and the ion flux decreases; if the thickness ratio of the composite membrane electrode layer and the two-dimensional material support layer is too large, that is, the thickness of the two-dimensional material support layer is too small, the ion transfer resistance decreases, the uniformity of the ion exchange membrane decreases, and the selectivity decreases.
[0172] It can be seen from the data results of Example 1 and Example 10 that if polyethyleneimine is not subjected to quaternization treatment, the ion flux and membrane selectivity will decrease.
[0173] It can be seen from the data results of Example 1 and Example 11 that if no aqueous solution additive is added to the aqueous solution in step (4), the uniformity of the polyamide layer is reduced and the lithium-magnesium separation coefficient is reduced.
[0174] It can be seen from the data results of Examples 1 and 12-13 that if the concentration of the aqueous solution additive in step (4) is too low, it will not play a significant role; if the concentration of the aqueous solution additive is too high, it will cover the nanopores on the surface of the polyamide layer and reduce the ion flux.
[0175] From the data results of Example 1 and Comparative Example 1, it can be seen that if the reduced graphene oxide support layer / ion exchange membrane layer is used as the membrane, the high Li + The interfacial concentration, compared with the integrated membrane, both the flux and selectivity are reduced.
[0176] It can be seen from the data results of Example 1 and Comparative Example 2 that if the composite membrane electrode layer only contains a membrane made of reduced graphene oxide, there is no obvious selectivity, and the fluxes of lithium and magnesium are similar.
[0177] It can be seen from the data results of Example 1 and Comparative Example 3 that if the electrochemical adsorption layer does not contain a two-dimensional material support layer, the density of the membrane decreases, and although the lithium-magnesium flux increases significantly, the lithium-magnesium separation coefficient decreases significantly.
[0178] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A lithium ion electrically controlled adsorption separation membrane, characterized in that: The lithium ion electrically controlled adsorption separation membrane comprises an electrochemical adsorption layer and an ion exchange membrane layer; The electrochemical adsorption layer comprises a composite membrane electrode layer and a two-dimensional material support layer stacked in sequence, and the two-dimensional material support layer is connected to the ion exchange membrane layer; The composite membrane electrode layer is obtained by compounding an electrode active material and a two-dimensional material.
2. The lithium ion electrically controlled adsorption separation membrane according to claim 1, characterized in that: The thickness ratio of the electrochemical adsorption layer to the ion exchange membrane layer is (1-10):
1.
3. The lithium ion electrically controlled adsorption separation membrane according to claim 1, characterized in that: The electrode active material includes LiMn2O4, LiNixCo y Mn z Any one of O2, Li2MnO3, MnO2 or LiFePO4, or a combination of at least two thereof.
4. The lithium ion electrically controlled adsorption separation membrane according to claim 1, characterized in that: The electrode active material has a multi-level pore structure.
5. The lithium ion electrically controlled adsorption separation membrane according to claim 1, characterized in that: The particle size D50 of the electrode active material is 50-400 nm.
6. The lithium ion electrically controlled adsorption separation membrane according to claim 1, characterized in that: The mass ratio of the electrode active material to the two-dimensional material support layer is (1-10):
1.
7. The lithium ion electrically controlled adsorption separation membrane according to claim 1, characterized in that: The material of the two-dimensional material and the material of the two-dimensional material support layer are independently reduced graphene oxide or MXene.
8. The lithium ion electrically controlled adsorption separation membrane according to claim 1, characterized in that: The thickness ratio of the composite membrane electrode layer and the two-dimensional material support layer is (1-5):
1.
9. The lithium ion electrically controlled adsorption separation membrane according to claim 1, characterized in that: The ion exchange membrane layer is a polyamide separation layer.
10. The lithium ion electrically controlled adsorption separation membrane according to claim 1, characterized in that: The average pore size of the ion exchange membrane layer is 0.2-1.5 nm.
11. A method for preparing a lithium ion electrically controlled adsorption separation membrane according to any one of claims 1 to 10, characterized in that: The preparation method comprises the following steps: (1) coating a two-dimensional material solution on a base film to form a two-dimensional material support layer on the base film; (2) coating a two-dimensional material solution containing an electrode active material on the two-dimensional material support layer to obtain an electrochemical adsorption layer having a composite membrane electrode layer; (3) Mixing the aqueous phase monomer material, the oil phase monomer material and the electrochemical adsorption layer to carry out an interfacial polymerization reaction to obtain a lithium ion electrically controlled adsorption separation membrane having an ion exchange membrane layer.
12. The preparation method according to claim 11, characterized in that: The material of the base film in step (1) is selected from any one of cellulose acetate, polyethersulfone or polyacrylonitrile, or a combination of at least two of them.
13. The preparation method according to claim 11, characterized in that: The coating method in step (2) includes vacuum filtration.
14. The preparation method according to claim 11, characterized in that: After the coating in step (2) is completed, the composite membrane electrode layer is irradiated by ultraviolet light source.
15. The preparation method according to claim 11, characterized in that: The aqueous phase monomer material in step (3) is an amine polymer.
16. The preparation method according to claim 11, characterized in that: The aqueous phase monomer material in step (3) is an amine polymer containing a quaternary amine group.
17. The preparation method according to claim 16, characterized in that: The preparation method of the amine polymer containing quaternary amine groups comprises: The amine polymer and the halogenating agent are mixed in an aqueous solution and subjected to a quaternary amination reaction to obtain the amine polymer containing a quaternary amine group.
18. The preparation method according to claim 15, characterized in that: The amine polymer includes any one of polyethyleneimine, piperazine, m-phenylenediamine, polyallylamine, p-phenylenediamine or hexamethylenediamine, or a combination of at least two thereof.
19. The preparation method according to claim 16, characterized in that: The amine polymer containing quaternary amine groups includes quaternized polyethyleneimine and / or quaternized polyallylamine.
20. The preparation method according to claim 17, characterized in that: The halogenating agent includes ethylamine bromide and / or propylamine bromide.
21. The preparation method according to claim 17, characterized in that: The mass ratio of the halogenating agent to the amine raw material is 1:(8-12).
22. The preparation method according to claim 17, characterized in that: The temperature of the quaternization reaction is 60-100°C.
23. The preparation method according to claim 17, characterized in that: The quaternization reaction time is 4-24h.
24. The preparation method according to claim 11, characterized in that: The oil phase monomer material in step (3) is an acyl chloride compound.
25. The preparation method according to claim 24, characterized in that: The acyl chloride compound includes any one of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride or tetraphthaloyl chloride, or a combination of at least two thereof.
26. The preparation method according to claim 11, characterized in that: The mass ratio of the aqueous phase monomer material to the oil phase monomer material in step (3) is (8-12):
1.
27. The preparation method according to claim 11, characterized in that: The mixing method in step (3) includes: The electrochemical adsorption layer with the composite membrane electrode layer is immersed in the aqueous phase solution containing the aqueous phase monomer material. After the immersion, the oil phase solution containing the oil phase monomer material is placed on the support layer side of the immersed electrochemical adsorption layer to perform an interfacial polymerization reaction.
28. The preparation method according to claim 11, characterized in that: The temperature of the interfacial polymerization reaction in step (3) is 20-25°C.
29. The preparation method according to claim 11, characterized in that: The time of the interfacial polymerization reaction in step (3) is 1-3 minutes.
30. The preparation method according to claim 27, characterized in that: The aqueous phase solution also contains an aqueous phase solution additive.
31. The preparation method according to claim 27, characterized in that: The aqueous solution additives include organic additives and / or inorganic additives.
32. The preparation method according to claim 31, characterized in that: The inorganic additives include LiCl and / or MgCl2.
33. The preparation method according to claim 31, characterized in that: The organic additive is an amphoteric organic additive, and the amphoteric organic additive includes any one of nonylphenol polyoxyethylene ether, dodecasodium phytic acid, sodium dodecyl sulfonate or hexadecyltrimethylammonium bromide.
34. The preparation method according to claim 30, characterized in that: In the aqueous phase solution, the mass concentration of the aqueous phase solution additive is 0.1-1%.
35. Use of the lithium ion electrically controlled adsorption separation membrane as claimed in any one of claims 1 to 10 in the development of low-grade lithium resources.
Citation Information
Patent Citations
Ion imprinting material for adsorbing lithium ions and preparation method thereof
CN115400743A
Positively charged composite nanofiltration membrane as well as preparation method and application thereof
CN115845640A